2017
DOI: 10.7860/jcdr/2017/23871.10231
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Spectrum of Duodenal Biopsies in Malabsorption: A Study from Southern India

Abstract: A constellation of clinical, serological, endoscopic and histopathologic features is essential in diagnosing CD and autoimmune duodenitis. Biopsy is also a useful tool in diagnosing infectious duodenitis that are missed in other investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 26 publications
7
22
3
Order By: Relevance
“…Worrall et al and Rustgi et al in their studies observed that the genetic haplotypes of CD can be seen in SLE patients also [16] [17]. Celiac disease has occurred in 14 case reports simultaneously with lupus and a possible link has been established between the common haplotypes HLA DR3 and HLA B8 seen in both diseases [18] [19]. In our study, 2 SLE patients, who satisfied the ACR criteria were subsequently diagnosed to have celiac disease.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Worrall et al and Rustgi et al in their studies observed that the genetic haplotypes of CD can be seen in SLE patients also [16] [17]. Celiac disease has occurred in 14 case reports simultaneously with lupus and a possible link has been established between the common haplotypes HLA DR3 and HLA B8 seen in both diseases [18] [19]. In our study, 2 SLE patients, who satisfied the ACR criteria were subsequently diagnosed to have celiac disease.…”
Section: Discussionsupporting
confidence: 48%
“…Patients with other autoimmune diseases may be under immunosuppressive management and this may result in subclinical manifestation of CD by clinical, serological and histopathological findings. In view of overlap of clinical and serological findings in CD and other autoimmune diseases, close observation of endoscopic findings for scalloped margins and biopsy findings of villous blunting and increased IELs is crucial in the differential diagnosis[19].In this context in our study, mild villous blunting was seen in one case of autoimmune duodenitis, however the IEL counts were normal while all the patients of CD had moderate to severe villous blunting. IELs were raised (>25/100 enterocytes) in 6 patients of autoimmune duodenitis.…”
mentioning
confidence: 49%
“…In present study, villi architecture was normal in 71 (71.7%) cases. Earlier studies by Balasubramanian P et al (14) reported normal villi architecture in 40.6% cases. Endoscopic duodenal nodularity was found in 16.6% cases in our study which are quite similar to study conducted by Castro F et al [16].…”
Section: Discussionmentioning
confidence: 86%
“…However, A study from south India with 101 patients of malabsorption, reported prevalence of celiac disease was 15.8%. (14) Major histopathological features of untreated celiac disease in duodenal biopsies are intraepithelial lymphocytosis, increased number of inflammatory cells at lamina propria and villous atrophy [15]. Howeverdiagnostic yield of routine duodenal biopsy for celiac disease was low as reported by Castro F et al, Stoven SA et al [8,16].…”
Section: Discussionmentioning
confidence: 98%
“…4-5µm thick sections taken and were stained with hematoxylin and eosin stain. 6 Immunohistochemistry (IHC) CD3 was done for all cases. The antibodies and chemicals were procured from Dako, Denmark (Rabbit Anti-CD3 Monoclonal Antibody (Clone EP41).…”
Section: Methodsmentioning
confidence: 99%